Acute Renal Infection in Adult, Part 1: An Overview of What the Radiologist Needs to Know - Hazarika, Suman; Venkataramanan, Rochita; Das, Tonmoy; Deuri, Sukanya; Lohchab, Shalini; Rongpipi, Tamsir; Agarwala, Asish; Venkataramanan, Akash (Journal of Gastrointestinal and Abdominal Radiology, 2019)
Acute renal infection or acute pyelonephritis (AP) denotes the process of inflammation of the renal parenchyma and its collecting system and the urothelium following infection. Uncomplicated AP commonly affects otherwise healthy, young women without structural or functional urinary tract abnormalities and without relevant comorbidities. More severe and complicated AP occurs in patients with a structurally or functionally abnormal genitourinary tract, or in persons with a predisposing medical condition like immune compromised state and diabetes. Complicated AP is characterized by a broader spectrum of clinical presentations, a wider variety of infecting organisms, and a greater risk of progression to a complication, such as intrarenal or perinephric abscess or emphysematous pyelonephritis and has the capacity to damage the organ and at times maybe life threatening. Role of imaging in renal infection is secondary, and in most situations, imaging is done to confirm the clinical diagnosis, map progression of disease in immune-compromised group of patients, or to evaluate for potential complications and therapeutic interventions. This article attempts to discuss the pathophysiology of AP from the standpoint of medical imaging and also brings out illustrative examples of various manifestations of AP and its complications. It provides imaging insight into various stages of inflammation, development of complication, and a roadmap for understanding AP through cross-sectional imaging.
Keywords: acute pyelonephritis; papillary necrosis; pyonephrosis; renal abscess